Length-weight relationship and reproductive activity of the Leporinus piau Fowler, 1941 captured in a small deactivated hydropower plant - doi: 10.4025/actascibiolsci.v35i3.17675 - Geraldo Eustáquio Valente Padilha; Júnia Aparecida Bernardes Afonso de Carvalho; Orion Boncompagni-Júnior; Fabrício Flávio Theophilo Domingos; Ralph Gruppi Thomé (Acta Scientiarum. Biological Sciences, 2013)
Reproductive activity of ‘piau gordura’ Leporinus piau was studied using biometric, macroscopic and microscopic analysis. A total of 74 specimens of L. piau were collected quarterly from January to December 2005 in a small deactivated  hydropower plant located at Jorge Pequeno Stream and preserved in a fixative solution until analysis. The alterations after fixation were evaluated. The stages of gonadal maturation were determined by histology and gonadosomatic index (GSI). The females and males in the spawning capable and regressing stage were registered from October to December. L. piau is total spawning and the HSI (hepatossomatic index), SRI (stomach repletion index) and CFI (coelomic fat index) of females and males did not showed a statistical difference. However they were numerically different between the stages of maturation. For both sexes, the smallest specimens captured during the reproductive activity have measured around 8.3 cm in total standard. The length-weight relationship observed for the parameter ‘b’ was 3.01 and the parameter ‘a’ was 0.02. This study demonstrates the importance of Jorge Pequeno Stream in the reproductive activity of migratory fish in the upper São Francisco river.